Antioxidant effects of ellagic acid on testicular tissue of rats exposed to tobacco smoke - Kaya, Nalan; Ozan, Gonca; Ozlem Dabak, Durrin; Gur, Seyfettin; Enver Ozan, Ibrahim (Annals of Medical Research, 2021)
Aim: Tobacco smoke negatively affects the male reproductive system. Ellagic acid (EA) has protective effects against oxidative damage. The aim of the study was to examine the protective effects of EA on testis of rats exposed to tobacco smoke.Materials and Methods: Twenty-four male Spraque-Dawley rats were divided into 4 groups (n=6): Control, tobacco smoke (TS), tobacco smoke+corn oil (TS+C) and tobacco smoke+ EA (TS+EA). TS, TS+C and TS+EA groups were exposed to tobacco smoke 1 hour twice a day and EA was applied 12 mg/kg every other day. Testis tissues were removed. eNOS immunohistochemical stain and TUNEL methods were applied. Biochemical analyzes and sperm analyzes were performed.Results: Degeneration in germinative epithelium, cell debris in the seminiferous tubule lumen, seperation in basement membrane, atrophic tubules, vascular congestion and edema in interstitial area were observed in TS and TS+C groups. Increased apoptotic cells and eNOS immunreactivity were observed in TS and TS+C groups. EA administration caused a decrease in histological alterations, eNOS immunreactivity and apoptotic cells. Increased MDA levels, decreased CAT and GSH-Px activities were observed in TS and TS+C groups. MDA levels decreased, CAT and GSH-Px activities increased in TS+EA group. A significant increase in the amount of abnormal sperm was detected in TS and TS+C groups. The reduction in the amount of abnormal sperm was detected in TS+EA group.Conclusions: Exposure to TS led to marked alterations on testes tissue and treatment with EA might prevent these toxic effects.Keywords: Tobacco Smoke; Testis; Ellagic Acid; Rat; TUNEL.
Keywords: Tobacco Smoke; Testis; Ellagic Acid; Rat; TUNEL.